2003
DOI: 10.1029/2002gl016624
|View full text |Cite
|
Sign up to set email alerts
|

Long‐duration hectometric type III radio bursts and their association with solar energetic particle (SEP) events

Abstract: It has recently been suggested by Cane et al. [2002] that a class of type III solar radio bursts, called type III‐l, is reliably associated with intense solar energetic particle (SEP) events. They proposed that the causative electrons for these bursts are accelerated in regions of reconnecting magnetic field in the wakes of coronal mass ejections (CMEs). In this paper, we examine the durations, intensities, and other characteristics of such radio bursts in the hectometric frequency range and compare them to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 8 publications
5
29
0
Order By: Relevance
“…The associated SEP events were clearly detected by GOES, even if the particle intensity was weak. This confirms the fact that flares, CMEs, metre wave type IV bursts and bright groups of DH type III bursts are necessarily associated with major SEP events, as observed by GOES, in line with earlier findings by Kahler (1982) for the type IV bursts and Cane, Erickson, and Prestage (2002) and MacDowall et al (2003) for the DH type III bursts. The situation is not the same for impulsive SEP events, which may occur without type IV emission, as shown in Klassen et al (2002), Maia and Pick (2004), and Klein and Posner (2005).…”
Section: Discussionsupporting
confidence: 91%
“…The associated SEP events were clearly detected by GOES, even if the particle intensity was weak. This confirms the fact that flares, CMEs, metre wave type IV bursts and bright groups of DH type III bursts are necessarily associated with major SEP events, as observed by GOES, in line with earlier findings by Kahler (1982) for the type IV bursts and Cane, Erickson, and Prestage (2002) and MacDowall et al (2003) for the DH type III bursts. The situation is not the same for impulsive SEP events, which may occur without type IV emission, as shown in Klassen et al (2002), Maia and Pick (2004), and Klein and Posner (2005).…”
Section: Discussionsupporting
confidence: 91%
“…Cane et al (2002) suggested that the complex type III bursts are indicative of large SEP events. MacDowall et al (2003MacDowall et al ( , 2009) confirmed the type III-SEP association. These association studies were thought to imply a flare acceleration mechanism for the SEP events.…”
Section: Low-frequency Type III Bursts Associated With Glessupporting
confidence: 56%
“…Earlier works report large occurrence rates of metric (∼90%) and DH type II bursts (100%) when associated with strong or major proton events, see e.g., Gopalswamy (2003); Cliver et al (2004); Cliver and Ling (2007). Interestingly, the same rates are reported for metric (100%) and DH type III bursts (∼90%) by Cane et al (2002);MacDowall et al (2003), respectively, again in relation to protons with large intensities. In a comprehensive analysis over SC23, Miteva et al (2013b) reported that the association between ∼25 MeV proton events and the DH type III is always present, followed by m and DH-II (75%) and m-IV (about 60%) bursts, see also their Table 4.…”
Section: Introductionsupporting
confidence: 53%